Routes and tours Industrial Designer and Researcher in the local business environment (Scenario: Pereira – Dosquebradas) (2019)
In this paper we review the experience and impact of industrial design inserted into the productive dynamic of some local companies at Risaralda, giving a chronological and situational its reality as a discipline since the dawn in the national industry, through the consolidation in the academy as a profession and finally adopted in regional locations where companies are beginning to articulate innovative responses from the research carried out by a young researcher as the linchpin between university, knowledge, enterprise, region.